Family Structure and Marital Violence among Women in Ghana - Tenkorang, Eric Y. (Journal of family violence, 2023)
The structure of Ghanaian families has significantly changed over the years. Even so, some features of the traditional Ghanaian family have remained. For instance, polygynous families continue to be common. This study examined relationships between family structure and intimate partner violence among women in Ghana. Specifically, we investigated differences in the IPV experiences of women in polygynous families compared to those in monogamous families, and we explored the mechanisms linking polygyny with IPV. We used data on 2,289 ever-married Ghanaian women aged 18 years and above and applied random-effects logit models to determine differences in the IPV risks for women in the two family structures. A higher proportion of women in polygynous families were unemployed than their comparators in monogamous families, and they had lower levels of education. They had limited autonomy and strong patriarchal values and were significantly more likely to experience physical, sexual, and emotional/psychological violence. Their IPV risk was exacerbated by their lack of socio-economic empowerment, limited autonomy, and strong belief in patriarchal norms. Net of these factors, polygynous women were still disadvantaged, pointing to existing unobserved differences between the two family structures or differences in family dynamics, with implications for IPV. We propose that policy makers provide educational and employment opportunities for women in general, while targeting polygynous women with specific interventions to improve their self-efficacy and autonomy.